Nutrition, immunity, and infectious diseases in the context of climate change and health syndemic: a scoping review for North America - M Banuet-Martínez; R Vriezen; S S Yamamoto; M J Espinosa-Romero; A Cunsolo; S L Harper (Environmental Research Letters, 2024)
Climate change exacerbates global food insecurity, leading to undernutrition and immunodeficiency, which in turn increases susceptibility to infectious diseases. In this way, climate change creates a syndemic, with undernutrition, immunity, and infectious disease risk adversely interacting. This scoping review aims to map: (1) trends in research about climate change impacts on food security; and (2) the extent to which food security is connected to the immune system and infectious diseases in published climate change research in North America. Using a scoping review process, we identified studies that described food security in the context of climate change in North America. A search string was developed and used to search five electronic databases for articles without language restriction. Data on food security pillars and their relationship with infectious diseases and the immune system were extracted from relevant articles and descriptively synthesized. We identified 204 published articles that met the inclusion criteria. The number of articles linking climate change to food security in North America increased yearly, with regional differences in the number of publications, climate variables analyzed, and study methods used. At least one connection between food security and the immune system or infectious diseases was discussed in 72 articles (35.3%). Of these, eleven articles mentioned both the immune system and infectious diseases and separately described their relationship with food security. However, only eight articles linked or described the relationship between food, immune systems, and infection—for example, by describing extreme weather events that reduced food security, resulting in malnutrition causing immunosuppression, thereby increasing the likelihood of infections. This highlights a gap in research on the adverse interaction between undernutrition, the immune system, and infectious disease risk in the context of climate change. This review underscores the need to study the interconnected and cascading health outcomes of climate change.